2020
DOI: 10.7554/elife.60853
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of sleep-courtship balance by nutritional status in Drosophila

Abstract: Sleep is essential but incompatible with other behaviors, and thus sleep drive competes with other motivations. We previously showed Drosophila males balance sleep and courtship via octopaminergic neurons that act upstream of courtship-regulating P1 neurons (Machado et al., 2017). Here we show nutrition modulates the sleep-courtship balance and identify sleep-regulatory neurons downstream of P1 neurons. Yeast-deprived males exhibited attenuated female-induced nighttime sleep loss yet normal daytime courtship, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Besides, P2 neurons, which include FB interneurons, regulate chronic isolation evoked sleep loss [ 31 ]. Moreover, courtship-regulator P1 neurons activate T1 neurons and modulate sleep/courtship balance based on the nutritional status [ 32 ]. Taking all the information mentioned above into account, we consider that arousal signals related to aggression, courtship, nutrition, and vision converge into the PB-FB pathway including FB interneurons to regulate arousal.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, P2 neurons, which include FB interneurons, regulate chronic isolation evoked sleep loss [ 31 ]. Moreover, courtship-regulator P1 neurons activate T1 neurons and modulate sleep/courtship balance based on the nutritional status [ 32 ]. Taking all the information mentioned above into account, we consider that arousal signals related to aggression, courtship, nutrition, and vision converge into the PB-FB pathway including FB interneurons to regulate arousal.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, P2 neurons, which include FB interneurons, regulate chronic isolation evoked sleep loss 34 . Moreover, courtship-regulator P1 neurons activate T1 neurons and modulate sleep/courtship balance based on the nutritional status 35 . Taking the abovementioned into account, we consider that arousal signals related to aggression, courtship, nutrition, and vision converge into the PB-FB pathway and pontine neurons to regulate arousal.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, P2 neurons, which include FB interneurons, regulate chronic isolation evoked sleep loss 34 . Moreover, courtshipregulator P1 neurons activate T1 neurons and modulate sleep/courtship balance based on the nutritional status 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the interaction between sleep and aggression, it has been shown that aggressive behaviors are suppressed in sleep-deprived male flies, and the changes are mediated by octopamine signaling (Kayser et al, 2015). Interestingly, Duhart and colleagues have recently reported that T1 neurons act downstream of courtship-and sleep-regulating P1 neurons to modulate nutrition-dependent sleep-courtship balance in male flies (Duhart et al, 2020). Elucidation of the mechanisms controlling the activity of T1 neurons may provide a novel link between sleep, aggression and courtship.…”
Section: Discussionmentioning
confidence: 99%